Clinical Outcomes Among Patients With Sickle Cell Disease and Transfusion-Dependent Beta-Thalassemia Treated With Allogeneic Hematopoietic Stem Cell Transplantation: A Systematic Literature Review - Nair R; Li N; Imren S; Kohli P; Lach K; Zhu L; Dudzic M (Journal of Blood Medicine)
Rajeshwari Nair,1 Nanxin Li,1 Suzan Imren,1 Puja Kohli,1 Krzysztof Lach,2 Lucía Zhu,2 Mirella Dudzic2 1Vertex Pharmaceuticals Incorporated, Boston, MA, USA; 2Maple Health Group LLC, New York, NY, USACorrespondence: Rajeshwari Nair, Vertex Pharmaceuticals Incorporated, 50 Northern Ave, Boston, MA, 02210, USA, Email Rajeshwari_Nair@vrtx.comBackground: The purpose of this study is to synthesize evidence on disease-specific outcomes in patients with sickle cell disease (SCD) or transfusion-dependent beta-thalassemia (TDT) following allogeneic hematopoietic stem cell transplant (allo-HSCT).Methods: A systematic literature review (SLR) was conducted in MEDLINE and Embase to identify publications up to May 2023, including patients with SCD or TDT treated with allo-HSCT. Occurrence of vaso-occlusive crises (VOCs) including acute pain, acute chest syndrome, priapism, and splenic sequestration in SCD, and red blood cell transfusion (RBCT) requirements in TDT were the main outcomes of interest. Transplant-related outcomes such as graft-versus-host disease (GVHD) and graft failure/rejection were summarized in the studies that reported main outcomes. Proportion of patients experiencing VOCs or RBCTs, GVHD, and graft failure/rejection after allo-HSCT were aggregated and descriptively reported with range across studies.Results: Thirty-one SCD studies met inclusion criteria. Twenty-nine studies assessed for VOC and pain crisis events after allo-HSCT; 11 studies reported ≥ 1 VOCs after allo-HSCT in 6.9% of the 2,760 patients. Graft failure was reported in 14.4% (0.9%– 18.8%, 14 studies) of patients, graft rejection in 5.5% (1.6%– 100.0%, 12 studies) of patients, acute GVHD in 22.4% (1.6%– 50.0%, 19 studies) of patients, and chronic GVHD in 20.4% (3.3%– 57.1%, 14 studies) of patients. Seventy-eight TDT studies met inclusion criteria. Fifty-six studies reported that 8.8% of the 3,107 patients required RBCTs after allo-HSCT. Graft failure was reported in 5.4% (1.1%– 80.0%, 21 studies) of patients, graft rejection in 7.5% (0.5%– 42.9%, 50 studies) of patients, acute GVHD in 28.4% (5.2%– 100.0%, 57 studies) and chronic GVHD in 15.2% (1.3%– 50.0%, 51 studies) of TDT patients.Conclusion: Based on this SLR, after allo-HSCT, a portion of patients with SCD continue to experience VOCs and a portion of patients with TDT continue to require RBCTs, in addition to experiencing GVHD and graft failure or rejection.Keywords: allogeneic HSCT, sickle cell disease, vaso-occlusive crisis, beta-thalassemia, transfusion dependent